Tatalaksana fiksasi terbuka dengan Plat vs Arm Sling pada fraktur midshaft klavikula: tinjauan pustaka sistematis - Anak Agung Gde Radityaningrat; Ketut Gede Mulyadi Ridia (DiscoverSys Inc., 2022)
Background: Clavicle fracture is one of the most common fractures according to the Allman and Robinson classification. In Indonesia, clavicle fractures account for 2.6-4% of all fractures in adults. There are two types of modalities in the treatment of clavicle fractures: operative and non-operative. This systematic literature review aims to compare the two modalities to see which treatment is better in terms of bone union time, pain score, assessing return of shoulder function after therapy, and complication rates for each treatment group. Methods: The strategy used is comparing several journals of non-operative and operative management for the midshaft clavicle fractures in adults. The selected reporting items is by using Systematic Review and Meta-Analysis Guidelines (PRISMA) to conduct comprehensive data collection. Results: The results are presented with a comparison of the ORIF Plate with the Arm Sling for treatment outcomes. This research identified 11 relevant articles on the comparison of ORIF Plate with Arm Sling for treating clavicle midshaft fractures in adults. The number of patients was 1,333 patients. These articles compared bone union time, pain scores, assessing post-therapy return of shoulder function, and complication rates. Conclusion: Operative management of midshaft clavicle displacement fracture with ORIF Plate gives better results than conservative management with Arm Sling. Latar Belakang: Fraktur klavikula merupakan salah satu fraktur yang sering di terjadi menurut klasifikasi Allman dan Robinson. Di Indonesia fraktur klavikula berkontribusi sebesar 2,6-4% dari seluruh fraktur pada orang dewasa. Terdapat dua jenis modalitas dalam tatalaksana fraktur klavikula yaitu dengan operatif dan non operatif. Tinjauan pustaka sistematis ini bertujuan untuk membandingkan kedua modalitas tersebut untuk melihat tatalaksana mana yang lebih baik dalam hal waktu tulang untuk menyatu (union), skor nyeri, menilai kembalinya fungsi bahu pasca terapi, dan tingkat komplikasi yang terjadi dari masing- masing kelompok terapi. Strategi yang digunakan adalah dengan membandingkan beberapa jurnal tatalaksana non operatif dan operatif untuk penanganan fraktur midshaft klavikula pada orang dewasa. Butir pelaporan yang dipilih menggunakan Tinjauan Sistematis dan Pedoman Meta-Analisis (PRISMA) untuk melakukan pengumpulan data yang komprehensif. Hasilnya disajikan dengan perbandingan antara ORIF plate dengan Arm Sling untuk hasil pengobatan. Penelitian ini mengidentifikasikan 11 artikel yang relevan tentang perbandingan antara ORIF Plate dengan Arm Sling untuk mengobati fraktur midshaft klafikula pada orang dewasa. Jumlah pasien sebanyak 1.333 pasien. Artikel – artikel tersebut membandingkan waktu tulang untuk menyatu (union), skor nyeri, menilai kembalinya fungsi bahu pasca terapi, dan tingkat komplikasi. Tatalaksana operatif pada fraktur displace midshaft clavicula dengan ORIF Plate memberikan hasil lebih baik dibandingkan dengan tatalaksana konservatif dengan Arm Sling.